Facile Green Synthesis of Zinc Oxide Nanoparticles and its Enhancement in Some Cotton Fabric Properties - AlHanash, Hana; Farhat, Amna; Issa, Ragiab; Alhanash, Fatma; Mohammed, Eenas; Hassan, Aicha (Wadi Alshatti University Journal of Pure and Applied Sciences, 2026)
An eco-friendly and facile method has been used for the synthesis of zinc oxide nanoparticles from Ficus carica (Fig) extract. The aqueous extract of (Fig leaves) was used as a reducing and capping agent in the synthesis of zinc oxide nanoparticles. The characterization using XRD, SEM, FTIR confirms the preparation of zinc oxide nanoparticles, ZnO NPs. The average particle size of the prepared ZnO nanoparticle was approximately 36.58 nm calculated from the XRD data. The prepared zinc oxide nanoparticles showed a spherical agglomerated porous nanostructure according to the SEM images. Further, cotton lawn fabrics were coated with zinc oxide nanoparticles via a simple technique using less chemicals, the coated cotton outperforms uncoated cotton in terms of thermal stability and abrasion resistance.